Fronto-medial electrode placement for electroconvulsive treatment of depression - Steele, J. Douglas; Farnan, Tom; Semple, David M.; Bai, Siwei (Frontiers in Neuroscience, 2022)
Electroconvulsive therapy (ECT) is the most effective treatment for severe treatment-resistant depression but concern about cognitive side-effects, particularly memory loss, limits its use. Recent observational studies on large groups of patients who have received ECT report that cognitive side-effects were associated with electric field induced increases in hippocampal volume, whereas therapeutic efficacy was associated with electric field induced increases in sagittal brain structures. The aim in the present study was to determine whether a novel fronto-medial ECT electrode placement would minimise electric fields in bilateral hippocampi whilst maximising electric fields in dorsal sagittal cortical regions. An anatomically detailed computational head model was used with finite element analysis, to calculate ECT-induced electric fields in specific brain regions identified by translational neuroimaging studies of treatment-resistant depressive illness, for a range of electrode placements. As hypothesised, compared to traditional bitemporal electrode placement, a specific fronto-medial electrode placement reduced bilateral hippocampal electric fields two-to-three-fold, whilst the electric fields in the dorsal anterior cingulate were increased by approximately the same amount. We highlight the clinical relevance of this specific fronto-medial electrode placement for ECT, which may significantly reduce cognitive and non-cognitive side-effects and suggest a clinical trial is indicated.